2010
DOI: 10.1177/1420326x10377545
|View full text |Cite
|
Sign up to set email alerts
|

Occupant’s Perception and Preference of Thermal Environment in Free-running Buildings in China

Abstract: The purpose of this paper was to present the occupants’ perception and preferences of thermal environments in free-running buildings in China. A study of the thermal environments in eight university dormitory buildings was conducted from September 2008 to July 2009 in Chongqing, China. A total of 1829 returned questionnaires were collected. Indoor and outdoor air temperatures, relative humidity and air velocities were measured while the questionnaire surveys were conducted. The scores were given based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Results indicated that the HVAC systems generated a comfort expectation for users, adjusting the comfort zone to warmer in winter and cooler in summer [308]. A research project conducted in naturally ventilated university dormitories in China demonstrated that user have a higher tolerance of temperature and that the effect of humidity on thermal comfort at high and low temperatures should not be ignored [309]. Sekhar and…”
Section: Page 30 Of 75mentioning
confidence: 97%
“…Results indicated that the HVAC systems generated a comfort expectation for users, adjusting the comfort zone to warmer in winter and cooler in summer [308]. A research project conducted in naturally ventilated university dormitories in China demonstrated that user have a higher tolerance of temperature and that the effect of humidity on thermal comfort at high and low temperatures should not be ignored [309]. Sekhar and…”
Section: Page 30 Of 75mentioning
confidence: 97%
“…Figure 1 shows the interior space of both Chinese and International student rooms. As noted by Li et al (2010) general residential buildings compared to dormitory buildings are characteristically small with a high occupant density but without heating ventilation and air-conditioning (HVAC), indicating that the indoor thermal environment in dormitory buildings would be generally worse than normal residential buildings in China, especially in winter or summer season. In our study this can present a different scenario in winter.…”
Section: Dormitory Buildings and Location Of Measuring Devicesmentioning
confidence: 99%
“…For example, in typical university dormitory buildings in Harbin, China, a severe cold region (Ning et al, 2016), Beijing campus buildings (Cao et al, 2014), naturally ventilated (NV) buildings in a hot-humid area (Y. Zhang et al, 2010), hot-humid climate in summer in dormitories of a university (He et al, 2016), severe cold winter and hot summer in university dormitories (Li et al, 2010) and humid areas (Cheng et al, 2008) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations